Comparative cardiovascular outcomes of semaglutide to dulaglutide in patients with type 2 diabetes - Takefumi Kishimori; Takao Kato; Atsuyuki Wada; Akira Tani; Ryosuke Yamaji; Jumpei Koike; Yoshihiro Iwasaki; Takehiro Matsumoto; Takafumi Yagi; Masaharu Okada (Scientific Reports)
Abstract Type 2 diabetes significantly increases cardiovascular risk. Glucagon-like peptide-1 receptor agonists (GLP-1 RA) reduce major adverse cardiovascular events, heart failure hospitalizations, and death. However, the comparison among GLP-1 RAs on cardiovascular outcomes is limited. We compared all-cause death and cardiovascular events in patients using semaglutide or dulaglutide in patients with type 2 diabetes. This retrospective observational study used the TriNetX database of deidentified electronic medical records from January 1, 2018, to December 31, 2020. We identified 4,691,652 patients with type 2 diabetes, among whom 231,075 initiated semaglutide and 189,103 initiated dulaglutide. After propensity score matching, 171,105 patients were included in each group. The primary outcome measure was all-cause death during the 3-year follow-up period.; secondary outcomes were acute myocardial infarction, stroke, and acute heart failure.Over 3 years, the risk for all-cause death in patients who received semaglutide relative to those who received dulaglutide was significantly lower (4.2% vs. 5.6%, p < 0.001; hazard ratio [HR] 0.75; 95% confidence interval [CI] 0.72–0.78). Similarly, patients who received semaglutide were less likely to have acute myocardial infarction (5.2% vs. 5.6%; HR, 0.94; 95% CI, 0.91–0.97; p < 0.001), stroke (5.8% vs. 6.4%; HR, 0.90; 95% CI, 0.87–0.93; p < 0.001), and acute heart failure (5.3% vs. 6.1%; HR, 0.88; 95% CI, 0.85–0.91; p < 0.001).In this multicenter, retrospective, observational study, semaglutide was associated with lower 3-year risks of all-cause death, acute myocardial infarction, stroke, and acute heart failure compared with dulaglutide in patients with type 2 diabetes.